A possible mode of survival of Fnsarium udum as a Mycoparasite - R. S. Upadhyay; Bharat Rai; R. C. Gupta (Acta Mycologica, 2014)
Survival of Fusarium udum Butler, the will pathogen of pigeon-pea, on other microfungi as a mycoparasite has been observed.